Some Longitudinal Results of the Belgian Socio-Economic Panel - Deleeck, H.; Cantillon, B.; Meulemans, B.; Van den Bosch, K. (Journal of Income Distribution®, 1993)
In this paper we present some important results on poverty in longitudinal perspective, based on two waves (1985 and 1988) of the Belgian Socio-Economic Panel, a household panel survey. The most important finding is that the number of longer term poor turns out to be considerably smaller than (about half as small as) the number of poor at one moment in time. We also investigate the characteristics of the longer term poor, as well as the incidence and outcomes of some important life events in terms of income, welfare, and poverty. The results are briefly compared with those for other European countries.